2004
DOI: 10.1104/pp.104.045195
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of Programmed Cell Death in Post-Phloem Transport Cells of the Maternal Pedicel Tissue in Developing Caryopsis of Maize

Abstract: We present cellular-and ultracellular-level studies here to show developmental programmed cell death (PCD) of placentochalazal (P-C) cell layers in maternal pedicel tissue in developing caryopses of normal seed (Mn1) and in the invertasedeficient miniature (mn1) seed mutant in maize (Zea mays). PCD was evidenced by loss of nuclei and all subcellular membranous organizations in many P-C layers. The terminal deoxynucleotidyl transferase-mediated X-dUTP nick-end labeling (TUNEL) stain that is diagnostic of apopto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
83
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 69 publications
(90 citation statements)
references
References 39 publications
(48 reference statements)
6
83
1
Order By: Relevance
“…Related to our finding, the loss-of-function of CWIN in the maize mutant mn1 led to a reduction of cell division and expansion in the mutant endosperm (Vilhar et al, 2002) and induction of PCD in the placentochalazal region of kernels (Kladnik et al, 2004). In our case, however, LMHS increased tomato fruit abortion in the wild type through triggering PCD (Figs.…”
Section: Elevated Cwin Activity Enhances Tomato Fruit Set Under Lmhscontrasting
confidence: 43%
“…Related to our finding, the loss-of-function of CWIN in the maize mutant mn1 led to a reduction of cell division and expansion in the mutant endosperm (Vilhar et al, 2002) and induction of PCD in the placentochalazal region of kernels (Kladnik et al, 2004). In our case, however, LMHS increased tomato fruit abortion in the wild type through triggering PCD (Figs.…”
Section: Elevated Cwin Activity Enhances Tomato Fruit Set Under Lmhscontrasting
confidence: 43%
“…5B) and its pigment strand is highly saturated by suberin and phenolics. This differentiation of the testa layers supports Kladnik et al's data (Kladnik et al 2004). Probably, the most important factor for quick germination is the structure of caryopsis attachment to the lemma-palea base.…”
Section: Variation In Dormancysupporting
confidence: 87%
“…Probably, the most important factor for quick germination is the structure of caryopsis attachment to the lemma-palea base. Kladnik et al (2004) found the different phenolics in a maize grain attachment structure. This area is free from suberin-phenolics in all ecotypes of annual B. distachyon (Fig.…”
Section: Variation In Dormancymentioning
confidence: 95%
“…4a). The peak of CK concentration before 12 DAP has been previously suggested to be associated with the induction of programmed cell death in the placento-chalazal region of the caryopsis pedicel (Rijavec et al, 2011), as its essential developmental phase (Kladnik et al, 2004). The proper activity of the placento-chalazal region is crucial for the transport of photosynthates from the maternal to the filial tissues of the caryopsis.…”
Section: Cytokinin Profiles and Transcript Levels Of Ck Metabolism Rementioning
confidence: 99%